Comparison of Analog Modulation and Demodulation Using MATLAB - Rustamaji; Muhammad Razu; ⁠Amanda Eka Adelia; Abnah Dwi Firmansyah (Journal of Engineering Science and Technology Management, 2026)
Analog communication systems remain foundational in applications such as radio broadcasting and low-power wireless transmission, where low-frequency signals require modulation to overcome bandwidth limitations and noise susceptibility. This study aims to compare the modulation-demodulation performance of Amplitude Modulation (AM), Frequency Modulation (FM), and Phase Modulation (PM) using MATLAB simulations in the time-frequency domain under varying Additive White Gaussian Noise (AWGN) conditions. Using a quantitative simulation-based comparative approach, the study evaluates three main analog modulation types across SNR variations of 10–30 dB with Nyquist-compliant sampling. The main instrument is MATLAB software; data analysis includes time-domain waveform comparison, FFT-based frequency spectrum analysis, and pre/post-demodulation SNR metrics. Results show that AM experiences significant waveform distortion at low SNR (10–20 dB), with narrow bandwidth but prominent sidebands in the frequency spectrum. FM and PM demonstrate superior demodulated waveform stability and greater noise resilience, despite wider bandwidth requirements consistent with Carson's rule. In conclusion, FM and PM are more suitable for noisy transmission channels, such as rural radio communication in Indonesia, providing a practical simulation-based reference for electrical engineering education and low-cost analog communication system design. Future work is recommended to extend validation toward analog-digital hybrid architectures using real hardware platforms such as Software-Defined Radio (SDR).